Relationships among workaholism, personality, obsessive beliefs, and entrepreneurial motivation - Rojin Ghasemijalal; María José Serrano-Fernández; Maria Boada-Cuerva; Beatriz Sora; Jordi Assens-Serra; Joan Boada-Grau (Frontiers in Psychology)
IntroductionRecent studies focusing mainly on entrepreneurial motivation have identified several variables (family security, motivation, and entrepreneurial intentions) as predictors of employee creativity. This research aims to provide insights into the underlying factors that shape entrepreneurial motivation, which can be used to develop effective strategies to support and foster entrepreneurship. In this study, we examine the relationship between workaholism, personality, obsessive beliefs and entrepreneurial motivation.MethodsThe study sample was comprised of 1,106 Spanish workers (48.51% men and 51.49% women) obtained through non-probability sampling.ResultsOur results showed that entrepreneurship motivation is related to personality traits. Positive relationships have been found with the variable perfectionism and intolerance of uncertainty, conscientiousness, work enjoyment, and agreeableness. Perfectionism and intolerance of uncertainty are the variables most strongly related to entrepreneurial motivation.DiscussionOur study contributes to the body of literature that examines the relationships between workaholism, personality, obsessive beliefs, and entrepreneurial motivation. The practical implications suggest that entrepreneurship support programs could benefit from considering not only entrepreneurial orientation but also other variables such as perfectionism and work enjoyment.